A Sustainable Integration Model (SIM) for Construction Project Management - Wajeeha Hasnain; Urooj Pasha (Journal of Management Practices, Humanities and Social Sciences, 2022)
Managing economic, social and environmental dimensions of sustainability in the operations of Construction Project Management is one of the significant tasks for today's managers. Because of its huge environmental impacts, The Construction industry emerges as an area of immense sustainable development. This led to an increase the focus of researchers and global communities towards incorporating sustainability in construction projects, and it changed the science of construction project management to a great extent. Yet, incorporating sustainability in projects is not a single time task rather a process whose scope is broadly distributed in all phases of construction projects, including planning, execution, delivery, and even till the lifecycle of project deliverables. Although project management and the concept of sustainability have been widely studied separately, how these two different fields act collectively and coordinate within the vibrant construction projects require more attention of researchers. In this paper Sustainability Integration Model (SIM) is presented based on a review of recent literature to define and incorporate sustainability in projects with a special focus on the construction industry.